2007
DOI: 10.1016/j.biopsych.2006.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Brain MAO A Activity Does Not Correspond to MAO A Genotype in Healthy Male Subjects

Abstract: Background-A functional polymorphism in the promoter region of the monoamine oxidase A (MAO A) gene has two common alleles that are referred to as the high and low MAO A genotypes. We report the first in vivo human study to determine whether there is an association between MAO A genotype and brain MAO A activity in healthy male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 25 publications
5
82
4
Order By: Relevance
“…140 A polymorphism located 1.2 kb upstream of the MAOA coding sequences (variable number tandem repeat; VNTR) was reported to affect the transcription of the MAOA promoter: alleles with 3.5 or 4 copies of the repeat sequence are transcribed 210 times more efficiently than those with 3 or 5 copies of the repeat, suggesting an optimal length for the regulatory region. 141 In contrast, a recent study reported that the genotype is not associated with MAOA activity, as measured by imaging techniques; 142 however, we suggest that this is not sufficient to rule out a role of the MAOA variations in psychiatric disorders. It can be hypothesized that a disrupted variation of a single enzyme is counteracted by the modulation of the signalling cascades that are associated with its activity.…”
Section: Monoamine Oxidase Acontrasting
confidence: 92%
“…140 A polymorphism located 1.2 kb upstream of the MAOA coding sequences (variable number tandem repeat; VNTR) was reported to affect the transcription of the MAOA promoter: alleles with 3.5 or 4 copies of the repeat sequence are transcribed 210 times more efficiently than those with 3 or 5 copies of the repeat, suggesting an optimal length for the regulatory region. 141 In contrast, a recent study reported that the genotype is not associated with MAOA activity, as measured by imaging techniques; 142 however, we suggest that this is not sufficient to rule out a role of the MAOA variations in psychiatric disorders. It can be hypothesized that a disrupted variation of a single enzyme is counteracted by the modulation of the signalling cascades that are associated with its activity.…”
Section: Monoamine Oxidase Acontrasting
confidence: 92%
“…One recent study positron emission tomography study of brain MAOA activity in relation to MAOA-LPR genotype suggests that genotype does not have a direct effect on transcriptional activity (Fowler et al, 2006). This finding may possibly be explained by the fact that the study did not take hormonal and/or environmental factors into account.…”
Section: Discussionmentioning
confidence: 98%
“…However, an important question remains concerning the point in time at which MAOA expression is thought to influence negative emotions and behavior. It is noteworthy that the relationship between MAOA genotype and in vivo MAOA activity remains unresolved (Fowler et al, 2007), and low MAOA levels in the brain may be a better predictor of trait aggressiveness than genotype (Alia-Klein, Goldstein, et al, 2008). Thus, the association of genotype and aggressive reactivity to provocation may not be because of MAOA functioning at the time of provocation.…”
Section: Discussionmentioning
confidence: 99%